RETRACTED: Modernization of production business processes of industrial enterprises using ARIMA and SARIMA models - Zhukov Aleksandr; Ponamareva Svetlana; Nikolayenko Andrey; Kartsan Igor (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001